Ultrasound-versus visual-guided transversus abdominis plane block prior to transabdominal preperitoneal ingunial hernia repair. A retrospective cohort study. (November 2020) - Paasch, C.; Fiebelkorn, J.; De Santo, G.; Aljedani, N.; Ortiz, P.; Gauger, U.; Boettge, K.; Full, S.H.; Anders, S.; Hünerbein, M.
Abstract: Background: The transversus abdominis plane block is a regional anesthesia technique. Recently, its impact on early chronic pain and the cumulative need of analgesic medication following inguinal hernia repair is being monitored. In terms of effectiveness and patient safety, it remains unclear whether the approach should be conducted preoperatively through ultrasound guidance, or through intraoperative visual guidance.The study at hand aims to provide more evidence on this topic. Methods: A monocentric retrospective matched pair analysis was performed. The intraoperative visual guided and ultrasound guided -transversus abdominis plane block prior to inguinal hernia repair in transabdominal preperitoneal technique were consecutively compared in regard to analgesic effectiveness and complication rate. The data of individuals who were operated on from June 2007 to February 2019 were analyzed. The matching criteria were ASA-Score, Gender, Age ( ±6 years), and hernia size (<1, 5 cm, 1, 5-3 cm, >1, 5 cm). Results: A total of 116 patients were enrolled. Both groups were homogenous in terms of age, gender contribution, body mass index, ASA-Score, hernia type, and size. The pain score at the postoperative anesthesia care unit was lower in the ultrasound-guided-transversus abdominis plane group without being statistically significant (VAS-Score: 0.67 vs.0.84). Patients of the ultrasound-guided-transversus abdominis plane group received significantly less metamizole on the day of operation (1.29 g (0.96) vs. 1.68 g (0.70), p = 0.015). Conclusion: Due to our findings, we assume that the ultrasound-guided-transversus abdominis plane -Block may reduce postoperative pain and analgesic consumption more effectively than the visual-guided-transversus abdominis plane lock. Further prospective clinical trials are mandatory. Highlights: The TAP-Block can be performed ultrasound- and visual-guided. No TAP-Block related complications appeared among our 116 individuals. Ptients who received the ultrasound-guided transversus abdominis plane block needed significantly less metamizole on the day of operation.